A kind of power generation composite fiber, preparation method and application thereof
High-concentration metal micro-nano particle composite fibers prepared by using wet spinning or twin-screw extrusion in smart wearable devices, woven into fabrics and combined with conductive coils, solve the problems of limited battery life and high material consumption. , realizes continuous power supply and efficient power conversion in the face of lithium battery exhaustion or extreme environments.
Patent Information
- Application Number
- CN202210748485.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-29
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-06-29
AI Technical Summary
Existing smart wearable devices rely on lithium batteries for power supply, have limited battery life and are sensitive to the environment, and cannot continuously supply power in the exhaustion of lithium batteries or extreme environments. The existing thermoelectric materials and piezoelectric materials are inefficient when converting mechanical energy into electrical energy and High material consumption.
Composite fibers prepared by wet spinning or twin screw extrusion method, containing high-concentration metal micro-nano particles, braided into fabrics and combined with conductive coils, and use human body movement to convert mechanical energy into electrical energy, so as to achieve the generation of current without contact. Power generation function.
It realizes continuous power supply in the exhausted lithium battery or extreme environment. The fabric has excellent wearable performance and durability, and can continuously output voltage and current, providing stable electrical energy for electronic devices.
Smart Images

Figure BDA0003720361040000241 
Figure BDA0003720361040000251 
Figure BDA0003720361040000261
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy collection, and in particular to a method for preparing a power generation composite fabric and applications thereof. Background Art
[0002] In recent years, with the rapid development of computer technology and flexible electronic technology, smart wearable electronics have shown an explosive growth trend. These smart products have the characteristics of wearable, small size, light weight, and strong fashion sense. They are widely used in medical health monitoring, behavior detection and assisted sports, smart home, education and teaching and other fields. Smart wearable devices all require energy supply to maintain their working state. Lithium batteries are relatively small and more environmentally friendly. Most micro wearable devices are powered by lithium batteries. The battery life of lithium batteries is relatively limited. Once the battery is used up or you forget to bring a replacement battery, the device will be inoperable. In addition, lithium batteries have strict requirements on the working environment. Temperature conditions will affect the safety, performance and life of the battery. These problems limit the application of smart wearable devices.
[0003] It is urgent to develop an energy harvesting method to realize continuous power supply for wearable electronic devices when the battery is exhausted and there is no replacement battery, and to continuously power wearable electronic devices when the lithium battery cannot work in extreme environments. The human body is a huge energy reservoir with rich biochemical energy, biothermal energy and biomechanical energy. For a 69 kg adult, the energy generated by the human body through breathing, heating, blood transportation, arm movement, finger movement and walking can reach more than 100W. Therefore, if 1% of the human body's energy is converted into electrical energy to power electronic devices, the power supply problem when the battery is exhausted and there is no replaceable battery can be solved. Clothing, as the second layer of human skin, has been widely used for warmth and information transmission. Additional and built-in technologies give clothing a variety of functions, enabling humans to perceive the surrounding environment. Compared with film-based flexible devices, clothing has the advantages of high porosity, large specific surface area, excellent breathability and wearing comfort. Therefore, if clothes can be used to convert the mechanical energy generated by human daily behavior into the electrical energy required by electronic clothing, the problem of continuous power supply for electronic clothing can be solved.
[0004] Chinese patent application CN105742474A relates to a method for preparing a flexible carbon nanotube-polyaniline thermoelectric device, comprising: adding carbon nanotubes and sodium dodecylbenzene sulfonate to an HCl solution, ultrasonicating, crushing the cells, then adding aniline, ultrasonicating, stirring under ice bath conditions to obtain a carbon nanotube-aniline dispersion, dripping an HCl solution of ammonium persulfate, and obtaining a carbon nanotube-polyaniline dispersion after reaction; placing a fabric in a sodium hydroxide solution and heating it, then placing it in 60-90°C water and stirring it, taking it out, drying it, adding it to the carbon nanotube-polyaniline dispersion, ultrasonicating, drying it, and repeating the steps of fabric dipping and drying; cutting the dried polyester into rectangular strips, alternately fixing them on a flexible substrate, and connecting the rectangular strips in parallel with conductive fibers. However, thermoelectric materials use the temperature gradient in the environment to convert thermal energy into electrical energy. However, the device is relatively brittle, has a low permeability, and requires a large temperature gradient. The temperature gradient in the human body and living environment is generally low, so this type of self-powered device has a low efficiency and cannot play an important role in the energy supply of wearable electronic devices.
[0005] Chinese patent application CN112226867A discloses a method for preparing ultra-soft piezoelectric PVDF yarn using electrospinning technology and magnetron sputtering technology. First, PVDF is dissolved in DMF to prepare a spinning solution of a certain concentration; secondly, PVDF is coated on the surface of the conductive yarn using electrospinning technology to prepare a conductive yarn-PVDF piezoelectric film; finally, a conductive metal film is sputtered on the surface of the conductive yarn-PVDF piezoelectric film using magnetron sputtering technology to prepare a piezoelectric PVDF yarn.
[0006] Chinese patent application CN109104117A discloses a wearable fabric nanogenerator and its preparation method. A wearable nanogenerator based on a nanofiber core-spun yarn structure with piezoelectric friction and staggered friction power generation functions is designed. Copper-plated cotton yarn is used as a conductive electrode, and polyvinylidene fluoride (PVDF) and nylon 66 nanofibers are used as two friction materials respectively. The yarn-forming process of conjugated electrospinning nanofibers is used to obtain two nanofiber core-spun yarns coated with PVDF and nylon 66 respectively. The core-spun yarns are interwoven into nanofiber fabrics by a weaving method to obtain a wearable fabric nanogenerator.
[0007] Chinese patent application CN109750403A discloses a power-generating fabric, wearable device, and sensor based on a friction nanogenerator. The power-generating fabric includes: a first friction line, a second friction line, and an elastic axis, wherein the first friction line and the second friction line are woven along the elastic axis; wherein the contacting portion of the first friction line and the second friction line of the power-generating fabric has a different friction electrode sequence; the elastic axis is elastically stretched, and the first friction line and the second friction line are separated from each other; the elastic axis realizes elastic recovery, driving the first friction line and the second friction line to contact each other.
[0008] Although piezoelectric materials and triboelectric materials can effectively collect mechanical energy generated by human body movement, these two materials have high output voltages, but due to their high internal resistance, they will cause large energy losses. At the same time, they must have external contact such as pressing to convert mechanical energy into electrical energy when working, which easily causes material loss. Therefore, it is necessary to prepare a new self-generating device that can generate electricity while also meeting the following requirements: generating current without mutual contact to reduce material consumption.
[0009] Chinese patent application CN111076805A discloses a fully flexible electromagnetic vibration sensor based on a folded film, including a flexible coil, an insulating layer, a flexible annular magnetic film, a flexible circular magnetic vibrator and an elastic substrate. The flexible coil is located in the hollow between two layers of flexible annular magnetic films, and the upper and lower surfaces of the flexible coil are both insulating layers; the flexible circular magnetic vibrator is located in the hollow between the flexible coil, and the thickness is less than the total thickness of the two layers of flexible annular magnetic films, and the upper and lower surfaces are respectively connected to the elastic substrate fixed at the bottom and top of the sensor to form an inertial vibrator. However, the device is in a thin film state, and the film type has poor washability, poor tensile resistance, and poor wearability.
[0010] Although piezoelectric materials and triboelectric materials can effectively collect mechanical energy generated by human body movement, these two materials have high output voltages, but due to their high internal resistance, they will cause large energy losses. At the same time, they must have external contact such as pressing to convert mechanical energy into electrical energy when working, which easily causes material loss. Therefore, it is necessary to prepare a new self-generating device that can generate electricity while also meeting the following requirements: generating current without mutual contact to reduce material consumption.
[0011] Chinese patent application CN111076805A discloses a fully flexible electromagnetic vibration sensor based on a folded film, including a flexible coil, an insulating layer, a flexible annular magnetic film, a flexible circular magnetic vibrator and an elastic substrate. The flexible coil is located in the hollow between two layers of flexible annular magnetic films, and the upper and lower surfaces of the flexible coil are both insulating layers; the flexible circular magnetic vibrator is located in the hollow between the flexible coil, and the thickness is less than the total thickness of the two layers of flexible annular magnetic films, and the upper and lower surfaces are respectively connected to the elastic substrate fixed at the bottom and top of the sensor to form an inertial vibrator. However, the device is in a thin film state, and the film type has poor washability, poor tensile resistance, and poor wearability. Summary of the invention
[0012] In view of the above problems, the present invention provides a wearable power generation composite fiber and fabric for human body mechanical energy collection, which can convert human body mechanical energy into electrical energy to power electronic devices when the human body moves. The composite fiber is prepared by wet spinning or twin-screw extrusion, and the metal micro-nano particles of the obtained composite fiber have a high doping concentration, and the obtained composite fiber is woven into a fabric, which has excellent wearable performance (breathable, moisture permeable, washable, wear-resistant, tensile, standard mechanical testing, etc.), good durability and repeatability. At the same time, it has adaptability to extreme environments, such as human sweat, acidity, alkalinity, and high and low temperature extreme environments.
[0013] The specific technical solutions of the present invention are as follows:
[0014] 1. A method for preparing a composite fiber, comprising the following steps:
[0015] Compounding metal micro-nano particles and polymer base materials to obtain composite materials;
[0016] The composite material is subjected to wet spinning or twin-screw extrusion to obtain composite fibers.
[0017] 2. The method according to item 1, wherein the metal micro-nano particles are metal magnetic micro-nano particles, metal compound magnetic micro-nano particles and / or metal alloy magnetic micro-nano particles;
[0018] Preferably, the metal magnetic micro-nano particles are selected from one or more of the following: ferromagnetic particles, cobalt magnetic particles and nickel magnetic particles;
[0019] Preferably, the metal compound magnetic micro-nano particles are selected from one or more of the following: magnetic iron oxide particles (γ-Fe 2 O 3 , Fe 3 O 4 ), chromium dioxide magnetic particles (CrO 2 ), iron nitride magnetic particles (Fe 6 N2 ), strontium ferrite magnetic particles (SrFe 12 O 19 ), barium ferrite magnetic particles (BaFe 12 O 19 ) and cobalt-iron oxide magnetic particles (Co-Fe 2 O 3 and Co-Fe 3 O 4 );
[0020] Preferably, the metal alloy magnetic micro-nano particles are selected from one or more of the following: neodymium iron boron magnetic particles (Nd 2 Fe 14 B), iron cobalt nickel magnetic particles (FeCoNi), iron cobalt vanadium magnetic particles (FeCoV), neodymium nickel cobalt magnetic particles (NdNiCo), samarium cobalt magnetic particles (SmCo 5 and Sm 2 Co 17 ) and aluminum nickel cobalt magnetic particles (AlNiCo).
[0021] 3. The method according to item 1 or 2, wherein the particle size of the metal micro-nanoparticles is in the range of 0.005-250 μm, preferably 0.005-5 μm.
[0022] 4. A method according to any one of items 1 to 3, wherein the polymer substrate material is a thermoplastic polymer, preferably selected from one or more polymers selected from polymethyl methacrylate (PMMA), PMMA composites doped with fluorinated polymers (F-PMMA), styrene dimethyl methacrylate copolymers (SMMA), cycloolefin copolymers (COC), cycloolefin polymers (COP), polycarbonate (PC), polyphenylene sulfone resin (PPSU), polyether sulfone resin (PES), polyethylene imine (PEI), polystyrene (PS), polyamide resin (PA), polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), polyurethane (PU), styrene-ethylene / butylene-styrene block copolymers (SEBS), acrylonitrile-butadiene-styrene copolymers (ABS), polyvinylidene fluoride (PVDF), polyethylene glycol (PEG), polytrimethylene terephthalate (PTT) and polyether.
[0023] 5. The method according to any one of items 1 to 4, wherein the metal micro-nanoparticles account for 0.1-90% by mass in the composite material, preferably 80%-90%.
[0024] 6. The method according to any one of items 1 to 5, wherein, in the step of obtaining the composite material, the metal micro-nanoparticles and the polymer base material are chemically dissolved and / or physically blended to obtain the composite material. Preferably, the chemical dissolution is to dissolve the metal micro-nanoparticles and the polymer base material in a solvent, and then remove the solvent to obtain the composite material. Preferably, the solvent is selected from one or more of dimethylacetamide, chloroform, ether, acetone, N,N-dimethylformamide, ethylene glycol, propylene glycol, ethanol, isopropanol, ethyl acetate, cyclohexane and xylene.
[0025] 7. The method according to any one of items 1 to 6, wherein the rotation speed of the twin-screw main engine is 100-6000 r / min.
[0026] 8. The method according to any one of items 1 to 7, wherein in the step of preparing the composite material, after using twin-screw extrusion, a winding step is also included before obtaining the composite material, and preferably, the winding speed is 100-6000r / min.
[0027] 9. A composite fiber produced by the method according to any one of items 1 to 8.
[0028] 10. A composite fiber comprising metal micro-nano particles and a substrate, wherein the metal micro-nano particles are dispersed in the substrate, wherein the metal micro-nano particles account for 0.1-90% by mass in the composite fiber, preferably 80-90% by mass.
[0029] 11. The composite fiber according to item 9 or 10, wherein the composite fiber has a diameter of 20 to 500 μm, preferably 20 to 100 μm.
[0030] 12. The composite fiber according to any one of items 9 to 11, wherein the fracture stress of the composite fiber is 0.1-100.0 MPa, and preferably, the fracture strain of the composite fiber is 101-800%.
[0031] 13. The composite fiber according to any one of items 9 to 12, wherein the single-point remanence of a single fiber in the composite fiber after magnetization is 0.1-16 mT;
[0032] Preferably, the cross section of a single fiber in the composite fiber is selected from the following: circular, circular ring, triangle, triangular ring, rectangle, rectangular ring, polygonal ring and irregular shape.
[0033] 14. The composite fiber according to any one of items 9 to 13, wherein the metal micro-nano particles are metal magnetic micro-nano particles, metal compound magnetic micro-nano particles and / or metal alloy magnetic micro-nano particles;
[0034] Preferably, the metal magnetic micro-nano particles are selected from one or more of the following: ferromagnetic particles, cobalt magnetic particles and nickel magnetic particles;
[0035] Preferably, the metal compound magnetic micro-nano particles are selected from one or more of the following: magnetic iron oxide particles (γ-Fe 2 O 3 , Fe 3 O 4 ), chromium dioxide magnetic particles (CrO 2 ), iron nitride magnetic particles (Fe 6 N 2 ), strontium ferrite magnetic particles (SrFe 12 O 19 ), barium ferrite magnetic particles (BaFe 12 O 19 ) and cobalt-iron oxide magnetic particles (Co-Fe 2 O 3 and Co-Fe 3 O 4 );
[0036] Preferably, the metal alloy magnetic micro-nano particles are selected from one or more of the following: neodymium iron boron magnetic particles (Nd 2 Fe 14 B), iron cobalt nickel magnetic particles (FeCoNi), iron cobalt vanadium magnetic particles (FeCoV), neodymium nickel cobalt magnetic particles (NdNiCo), samarium cobalt magnetic particles (SmCo 5 and Sm 2 Co 17 ) and aluminum nickel cobalt magnetic particles (AlNiCo).
[0037] 15. A composite fiber according to any one of items 9 to 14, wherein the substrate is a thermoplastic polymer, preferably selected from one or more polymers selected from polymethyl methacrylate (PMMA), PMMA composite materials doped with fluorinated polymers (F-PMMA), styrene dimethyl methacrylate copolymers (SMMA), cycloolefin copolymers (COC), cycloolefin polymers (COP), polycarbonate (PC), polyphenylene sulfone resins (PPSU), polyether sulfone resins (PES), polyethylene imine (PEI), polystyrene (PS), polyamide resins (PA), polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), polyurethane (PU), styrene-ethylene / butylene-styrene block copolymers (SEBS), acrylonitrile-butadiene-styrene copolymers (ABS), polyvinylidene fluoride (PVDF), polyethylene glycol (PEG), polytrimethylene terephthalate (PTT) and polyethers, and more preferably styrene-ethylene / butylene-styrene block copolymers (SEBS).
[0038] 16. A composite fabric, wherein the composite fabric is obtained by weaving the composite fiber described in any one of items 9 to 15; preferably, the composite fiber is coated with cotton thread;
[0039] Preferably, the composite fabric is a plain fabric, a twill fabric, a satin fabric or a 3D spacer fabric structure;
[0040] Preferably, the composite fabric is a multi-color composite fabric;
[0041] Preferably, the composite fiber is obtained by coloring the composite fiber according to any one of claims 9 to 15 and then weaving the composite fiber.
[0042] 17. A power-generating fabric, wherein the power-generating fabric comprises the composite fabric of item 16, a conductive coil and a garment, wherein the composite fabric and the conductive coil are respectively arranged on the garment, preferably at relative positions of the garment, and generates power by utilizing the interaction during human body movement.
[0043] The power-generating fabric can generate electricity through the interaction of human body movements, such as the swinging of arms or the alternating movements of legs, thereby converting the mechanical energy of the human body into electrical energy to power electronic devices. When the human body is moving, the output voltage is: 0.1-30V, the output current is: 0.1-100mA, and the output power is 0.1-3W.
[0044] 18. The power-generating fabric according to item 17, wherein the conductive coil is selected from one or more of carbon fiber, carbon nanotube, Mxene, copper, aluminum, silver, gold, stainless steel wire, nickel and cadmium sulfide, iodide or oxide, polyacetylene, polyaniline, polypyrrole and polythiophene.
[0045] 19. The power-generating textile according to item 17 or 18, wherein the surface magnetism of the power-generating textile after magnetization is 0.1-35 mT.
[0046] Effects of the Invention
[0047] The composite fiber obtained by the present invention and the fabric prepared using the composite fiber have excellent wearable properties (breathable, moisture permeable, washable, wear-resistant, stretchable, standard mechanical test, etc.), good durability and repeatability.
[0048] The color of the composite fabric can be adjusted according to actual scene requirements and fashion needs to adapt to different application scenarios and meet different application needs.
[0049] The preparation process of the composite fiber and the fabric thereof is simple and can be mass-produced.
[0050] The composite fiber and the fabric thereof have excellent stability and can adapt to extreme environments.
[0051] The power-generating fabric prepared by using the composite fabric of the present invention can continuously output voltage and current, realize the power generation capacity of clothing, and thus provide power for electronic equipment in various fields. DETAILED DESCRIPTION
[0052] The present invention is described in detail below. Although specific embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0053] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0054] The present invention provides a method for preparing a composite fiber, which comprises the following steps:
[0055] Compounding metal micro-nano particles and polymer base materials to obtain composite materials;
[0056] The composite material is subjected to wet spinning or twin-screw extrusion to obtain composite fibers.
[0057] In one embodiment, the composite material is a composite material particle, a composite material film or a composite material powder.
[0058] In one embodiment, the metal micro-nano particles are metal magnetic micro-nano particles, metal compound magnetic micro-nano particles and / or metal alloy magnetic micro-nano particles;
[0059] Preferably, the metal magnetic micro-nano particles are selected from one or more of the following: ferromagnetic particles, cobalt magnetic particles and nickel magnetic particles;
[0060] Preferably, the metal compound magnetic micro-nano particles are selected from one or more of the following: magnetic iron oxide particles (γ-Fe 2 O 3 , Fe 3 O 4 ), chromium dioxide magnetic particles (CrO 2 ), iron nitride magnetic particles (Fe 6 N 2 ), strontium ferrite magnetic particles (SrFe 12 O 19 ), barium ferrite magnetic particles (BaFe 12 O 19 ) and cobalt-iron oxide magnetic particles (Co-Fe 2 O 3 and Co-Fe 3 O 4 );
[0061] Preferably, the metal alloy magnetic micro-nano particles are selected from one or more of the following: neodymium iron boron magnetic particles (Nd 2 Fe 14 B), iron cobalt nickel magnetic particles (FeCoNi), iron cobalt vanadium magnetic particles (FeCoV), neodymium nickel cobalt magnetic particles (NdNiCo), samarium cobalt magnetic particles (SmCo 5 and Sm 2 Co 17 ) and aluminum nickel cobalt magnetic particles (AlNiCo).
[0062] In one embodiment, the particle size of the metal micro-nano particles is in the range of 0.005-250 μm, preferably 0.005-5 μm.
[0063] By using the particle size range of the metal micro-nano particles described above, the diameter of the obtained fibers can be made finer, which is convenient for weaving, and the obtained power-generating fabric is closer to ordinary fabrics.
[0064] For example, the particle size of the metal micro-nano particles can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, etc.
[0065] When this type of particle is mixed with a polymer base material, the mixture can be more uniform and the prepared fibers can be thinner. The currently achieved thinnest fiber diameter is 20 μm, which can make the fibers have excellent elasticity and flexibility. The obtained fibers have good elasticity, and the fabric prepared using the fibers has good stretchability. The obtained fibers have good flexibility, the fabric has good flexibility, and the wearable performance is good.
[0066] In one embodiment, the polymer substrate material is a thermoplastic polymer, preferably selected from polymethyl methacrylate (PMMA), PMMA composites doped with fluorinated polymers (F-PMMA), styrene dimethyl methacrylate copolymers (SMMA), cycloolefin copolymers (COC), cycloolefin polymers (COP), polycarbonate (PC), polyphenylene sulfone resin (PPSU), polyether sulfone resin (PES), polyethylene imine (PEI), polystyrene (PS), polyamide resin (PA), polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), polyurethane (PU), styrene-ethylene / butylene-styrene block copolymers (SEBS), acrylonitrile-butadiene-styrene copolymers (ABS), polyvinylidene fluoride (PVDF), polyethylene glycol (PEG), polytrimethylene terephthalate (PTT) and one or more polymers selected from polyether.
[0067] Among them, polymethyl methacrylate (PMMA) is a frequently used glass substitute material due to its advantages of high transparency, low price, and easy machining.
[0068] Styrene dimethyl methacrylate copolymer (SMMA) is a polyacrylic acid resin copolymer.
[0069] Cyclic olefin copolymer (COC) is a high value-added thermoplastic engineering plastic made by the polymerization of cyclic olefins. Due to its high transparency, low dielectric constant, excellent heat resistance, chemical resistance, melt fluidity, barrier properties and dimensional stability, it is widely used in the manufacture of various optical, information, electrical and medical materials.
[0070] Cyclic olefin polymer (COP) is used for medical optical components and high-end pharmaceutical packaging materials. Its raw material characteristics are: high transparency, low birefringence, low water absorption, high rigidity, high heat resistance, good water vapor airtightness, and compliance with FDA standards.
[0071] Polycarbonate (PC) is a high molecular polymer containing carbonate groups in its molecular chain. It can be divided into various types according to the structure of the ester group, such as aliphatic, aromatic, aliphatic-aromatic, etc.
[0072] Polyphenylene sulfone resin (PPSU) is an amorphous thermoplastic with high transparency and high hydrolytic stability.
[0073] Polyethersulfone resin (PES) resin is a thermoplastic polymer material with excellent comprehensive properties. It has excellent heat resistance, physical and mechanical properties, insulation properties, etc., especially it can be used continuously at high temperatures and can maintain stable performance in environments with rapid temperature changes.
[0074] Usually an amorphous polymer, polyethersulfone has better melt processability and lower melt viscosity than polysulfone, small molding shrinkage (only about 0.6%) and good dimensional stability.
[0075] Polyetherimide (PEI) is a super engineering plastic made of amorphous polyetherimide. It has the best high temperature resistance and dimensional stability, as well as chemical resistance, flame retardancy, electrical properties, high strength, high rigidity, etc. It can be widely used in high temperature resistant terminals, IC bases, lighting equipment, FPCB (flexible printed circuit board), liquid delivery equipment, aircraft internal parts, medical equipment and household appliances, etc.
[0076] Polystyrene (PS) refers to a polymer synthesized from styrene monomers by free radical addition polymerization. It is a colorless and transparent thermoplastic with a glass transition temperature above 100°C, so it is often used to make various disposable containers that need to withstand the temperature of boiling water, as well as disposable foam lunch boxes.
[0077] Polypropylene (PP) is a thermoplastic synthetic resin with excellent performance. It is a colorless, translucent, thermoplastic, lightweight general-purpose plastic. It has chemical resistance, heat resistance, electrical insulation, high-strength mechanical properties, and good high-wear resistance processing properties.
[0078] "Fluorine-containing resin" is a type of thermoplastic resin containing fluorine atoms in its molecular structure. It has excellent high and low temperature resistance, dielectric properties, chemical stability, weather resistance, non-flammability, non-stickiness and low friction coefficient, and polyvinylidene fluoride is one of them.
[0079] Polyvinylidene fluoride (PVDF) mainly refers to vinylidene fluoride homopolymer or copolymer of vinylidene fluoride and other small amounts of fluorine-containing vinyl monomers. It has the characteristics of both fluorine-containing resins and general-purpose resins. In addition to having good chemical corrosion resistance, high temperature resistance, oxidation resistance, weather resistance, and radiation resistance, it also has special properties such as piezoelectricity, dielectricity, and hot spot properties.
[0080] Polyamide resin (PA) is a polycondensation polymer compound with a -CONH structure in the molecule, which is usually obtained by polycondensation of dibasic acid and diamine. The most prominent advantage of polyamide resin is that the softening point range is extremely narrow, unlike other thermoplastic resins, which have a gradual solidification or softening process. When the temperature is slightly lower than the melting point, it will cause rapid solidification.
[0081] Polyethylene (PE) is a thermoplastic resin obtained by polymerization of ethylene. In industry, it also includes copolymers of ethylene and a small amount of α-olefins. Polyethylene is odorless, non-toxic, feels like wax, has excellent low temperature resistance (the lowest operating temperature can reach -100℃~-70℃), good chemical stability, and can withstand the corrosion of most acids and alkalis (not resistant to oxidizing acids).
[0082] Polyethylene terephthalate (PET) is also commonly known as polyester resin. It is a condensation product of terephthalic acid and ethylene glycol. It is a crystalline saturated polyester. It is a milky white or light yellow, highly crystalline polymer with a smooth and shiny surface. It has good creep resistance, fatigue resistance, and friction resistance, low wear and high hardness. It has the greatest toughness among thermoplastics; it has good electrical insulation properties and is less affected by temperature.
[0083] Acrylonitrile resin (PAN) is mainly acrylonitrile, which provides good gas barrier, chemical resistance and gas and odor retention. This resin has medium tensile strength, good impact resistance when modified or oriented with rubber, and can be processed by extrusion, injection molding and thermoforming.
[0084] Polyvinyl alcohol (PVA) is a widely used water-soluble polymer with properties between those of plastics and rubber.
[0085] Polyvinyl chloride (PVC) is a polymer material obtained by addition polymerization of vinyl chloride.
[0086] Polyurethane (PU) is a polymer containing a urethane group (—NH—COO—) in its molecular structure, and the polyurethane includes thermoplastic polyurethane, preferably a thermoplastic polyurethane elastomer.
[0087] SEBS is a polystyrene-polybutadiene-polystyrene triblock copolymer.
[0088] Acrylonitrile-butadiene-styrene copolymer (ABS) is a thermoplastic polymer material with high strength, good toughness and easy processing.
[0089] Polyethylene glycol (PEG), also known as polyethylene oxide, refers to a polymer of ethylene oxide.
[0090] Polytrimethylene terephthalate (PTT), this material has the characteristics of both polyester and nylon.
[0091] In one embodiment, the metal micro-nano particles account for 0.1-90% by mass in the composite material, preferably 80-90%.
[0092] For example, in terms of mass percentage in the composite material, the metal micro-nano particles can be 0.1%, 5%, 10%, 20%, 30%, 50%, 70%, 75%, 80%, 85%, 90%, etc.
[0093] In one embodiment, in the step of obtaining the composite material, the metal micro-nano particles and the polymer base material are uniformly compounded by chemical dissolution mixing and / or physical blending steps. Preferably, the metal micro-nano particles and the polymer base material are chemically dissolved and mixed into a solvent for dissolution, and then the solvent is removed to obtain the composite material. Preferably, the solvent is selected from one or more of dimethylacetamide, chloroform, ether, acetone, dimethylformamide, ethylene glycol, propylene glycol, ethanol, isopropanol, ethyl acetate, cyclohexane and xylene.
[0094] The present invention does not impose any limitation on the method for removing the solvent, and those skilled in the art can confirm it as needed. For example, the solvent can be removed by vacuum drying. Preferably, the vacuum drying temperature is 80° C. and the drying time is 24 h.
[0095] Among them, dimethylacetamide (DMAC) is a non-protonic highly polar solvent with a slight ammonia smell and strong solubility. It can be mixed with water, aromatic compounds, esters, ketones, alcohols, ethers, benzene and chloroform, and can activate compound molecules. It is widely used as a solvent and catalyst.
[0096] Dimethylformamide (DMF) is a colorless, transparent liquid that is miscible with water and most organic solvents and is a commonly used solvent for chemical reactions.
[0097] The present invention does not impose any limitation on the physical blending method, for example, the metal micro-nano particles and the polymer base material are mixed by twin-screw extrusion.
[0098] In one embodiment, the twin-screw main engine speed is 100-6000r / min, and the extrusion temperature of the twin-screw is 210°C.
[0099] In one embodiment, in the step of preparing the composite material, after using twin-screw extrusion, a winding step is also included before obtaining the composite material. Preferably, the winding speed is 100-6000 r / min.
[0100] The method of the present invention uses two blending steps, the first one is solution blending, and the second one is high-speed rotating blending using a twin-screw, so that the doping concentration of metal micro-nano particles in the obtained composite fiber can reach up to 90%, and the obtained composite fiber has good strain performance.
[0101] In addition, the present invention uses twin-screw extrusion to achieve blending. Since the twin-screw extruder has high torque and high speed, the speed can reach 3000r / min, and the shear force applied to the material during preparation is relatively uniform. When processing elastomers with high viscosity such as SEBS and TPU, as the shear force increases, the viscosity decreases significantly, and is closer to the viscosity of the magnetic particles, so it can be more effectively fused to achieve a good blending effect.
[0102] In one embodiment, the wet spinning is to dissolve the polymer base material and the metal micro-nanoparticles in an organic solvent to form a spinning solution, and then spin to obtain a composite fiber; preferably, the spinning solution is extruded into a coagulation bath by an injection pump to obtain the composite fiber by exchanging the solvent and the coagulant; further preferably, the mixed solution obtained by the exchange of the solvent and the coagulant in the coagulation bath is coagulated and stretched to obtain the composite fiber.
[0103] In one embodiment, the wet spinning is to dissolve the metal micro-nano particles and the polymer substrate material in an organic solvent to form a spinning solution, and then extrude it from the injection pump into a coagulation bath through a stepper motor with set parameters. In the coagulation bath, the extruded polymer mixed solution is rapidly coagulated due to the exchange of the solvent and the coagulant. A stretching and traction device is set on the other side, and a polymer fiber with a relatively fine wire diameter can be obtained with the extrusion of the injection pump and the traction of the stretching device.
[0104] The method of the present invention is easy to add materials during the preparation process, and can add materials without restriction. It is suitable for materials with very high or very low viscosity, such as SEBS, TPU, PPS polyphenylene sulfide, etc.
[0105] The method of the present invention has no requirements on the shape of the added material, which can be a strip material, a paste material, a powder material, etc.
[0106] The method described in the present invention can shorten the residence time of the material in the twin-screw extruder by adjusting the screw length, and the residence time distribution is narrow, and the heat generated by friction is less. Therefore, the twin-screw extruder can be used to process heat-sensitive materials such as rigid polyvinyl chloride, polytrifluorochloroethylene, polyoxymethylene, heat-sensitive color-changing inks, etc.
[0107] The method of the present invention can effectively discharge air, water vapor, etc. in the material through drying, exhausting and other processes during the preparation process, reduce bubbles in the prepared fiber, and the prepared fiber has excellent density.
[0108] The method of the present invention can adjust the mixing time of materials inside the twin screws by adjusting the length of the screws, thereby making the mixing more uniform.
[0109] The wet spinning method of the present invention has a relatively fine fiber diameter, the fiber diameter is about 1-200 μm, and the fiber has good flexibility. The method is capable of producing magnetic composite fibers with a relatively fine fiber diameter and the preparation method is simple and fast.
[0110] The present invention provides a composite fiber, which is prepared by the above method.
[0111] The present invention provides a composite fiber, which comprises metal micro-nano particles and a substrate. The metal micro-nano particles are dispersed in the substrate, wherein the metal micro-nano particles account for 0.1-90% by mass in the composite fiber, preferably 80-90%.
[0112] For example, the metal micro-nano particles may account for 0.1%, 5%, 10%, 20%, 30%, 50%, 70%, 75%, 80%, 85%, 90%, etc., in terms of mass percentage in the composite fiber.
[0113] The higher the content of metal micro-nano particles in the composite fiber of the present invention, the higher the remanence will be, the stronger the magnetic properties will be, and the better the effect will be.
[0114] In one embodiment, the diameter of the composite fiber is 20-500 μm, preferably 20-100 μm.
[0115] For example, the diameter of the composite fiber may be 20 μm, 30 μm, 50 μm, 70 μm, 90 μm, 110 μm, 130 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, etc.
[0116] In one embodiment, the breaking stress of the composite fiber is 0.1-100.0 MPa. Preferably, the breaking strain of the composite fiber is 101-800%.
[0117] For example, the breaking stress of the composite fiber may be 0.1 MPa, 1 MPa, 5 MPa, 10 MPa, 15 MPa, 20 MPa, 50 MPa, 70 MPa, 90 MPa, 100 MPa, etc.;
[0118] The breaking strain of the composite fiber may be 101%, 150%, 200%, 250%, 300%, 400%, 500%, 600%, 700%, 800%, etc.
[0119] In one embodiment, the single-point remanence of a single fiber in the composite fiber after magnetization is 0.1-16 mT.
[0120] The single-point remanence refers to the residual magnetic induction intensity of the magnetic fiber after magnetization. The higher the single-point remanence, the stronger the magnetic performance and the better the effect.
[0121] For example, the single-point remanence of a single fiber in the composite fiber after magnetization can be 0.1mT, 1mT, 2mT, 3mT, 4mT, 5mT, 6mT, 7mT, 8mT, 9mT, 10mT, 11mT, 12mT, 13mT, 14mT, 15mT, 16mT, etc.
[0122] In one embodiment, the cross section of a single fiber in the composite fiber is selected from the following: circle, circular ring, triangle, triangular ring, rectangle, rectangular ring, polygonal ring and irregular shape.
[0123] In one embodiment, the metal micro-nano particles are metal magnetic micro-nano particles, metal compound magnetic micro-nano particles and / or metal alloy magnetic micro-nano particles;
[0124] Preferably, the metal magnetic micro-nano particles are selected from one or more of the following: ferromagnetic particles, cobalt magnetic particles and nickel magnetic particles;
[0125] Preferably, the metal compound magnetic micro-nano particles are selected from one or more of the following: magnetic iron oxide particles (γ-Fe 2 O 3 , Fe 3 O 4 ), chromium dioxide magnetic particles (CrO 2 ), iron nitride magnetic particles (Fe 6 N 2 ), strontium ferrite magnetic particles (SrFe 12 O 19 ), barium ferrite magnetic particles (BaFe 12 O 19 ) and cobalt-iron oxide magnetic particles (Co-Fe 2 O 3 and Co-Fe 3 O 4 );
[0126] Preferably, the metal alloy magnetic micro-nano particles are selected from one or more of the following: neodymium iron boron magnetic particles (Nd 2 Fe 14 B), iron cobalt nickel magnetic particles (FeCoNi), iron cobalt vanadium magnetic particles (FeCoV), neodymium nickel cobalt magnetic particles (NdNiCo), samarium cobalt magnetic particles (SmCo 5 and Sm 2 Co 17 ) and aluminum nickel cobalt magnetic particles (AlNiCo).
[0127] In one embodiment, the substrate is a thermoplastic polymer, preferably selected from polymethyl methacrylate (PMMA), PMMA composites doped with fluorinated polymers (F-PMMA), styrene dimethyl methacrylate copolymers (SMMA), cycloolefin copolymers (COC), cycloolefin polymers (COP), polycarbonate (PC), polyphenylene sulfone resin (PPSU), polyether sulfone resin (PES), polyethylene imine (PEI), polystyrene (PS), polyamide resin (PA), polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), polyurethane (PU), styrene-ethylene / butylene-styrene block copolymer (SEBS), acrylonitrile-butadiene-styrene copolymer (ABS), polyvinylidene fluoride (PVDF), polyethylene glycol (PEG), polytrimethylene terephthalate (PTT) and polyether. One or more polymers, more preferably styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0128] The composite fiber of the present invention has high remanence, good magnetic properties, and good strain properties.
[0129] The composite fibers obtained by the present invention can be prepared into composite fibers of various colors. For example, chemical methods or physical methods in existing industrial production processes can be used to achieve multiple colors of fibers to adapt to different application scenarios. For example, cotton yarns of various colors such as white, gray, black, yellow, red, blue, light blue, dark blue, green, cyan, and purple are used for coating, and then the coated yarns are woven using a rapier loom by warp and weft weaving to obtain a magnetic composite fabric.
[0130] The chemical method in the industrial production process includes one or more of: exhaust dyeing, roller dyeing, pad dyeing, leuco dyeing, suspension pad dyeing, and leuco acid dyeing, thereby achieving color diversification of the composite fiber.
[0131] The physical method in the industrial production process includes: utilizing one or more industrialized equipments such as existing covering machines, twisting machines and rope braiding machines in combination with fabrics commonly used in the textile industry to achieve color diversification of composite fibers.
[0132] The yarns commonly used in the textile industry in the physical method in the industrial production process include: one or more of cotton yarn, polyester, spandex, nylon, and acrylic.
[0133] The present invention provides a composite fabric, which is obtained by weaving the composite fiber described above. Preferably, the composite fiber is coated with cotton yarn, for example, cotton yarn of various colors such as white, gray, black, yellow, red, blue, light blue, dark blue, green, cyan, and purple is used for coating;
[0134] Preferably, the composite fabric is a plain fabric, a twill fabric, a satin fabric or a 3D spacer fabric structure.
[0135] The weaving is carried out using an existing industrial weaving method, and the structure of the composite fabric can be one or more of plain weave, twill weave, satin weave, variable weave, combined weave or complex weave.
[0136] The present invention provides a power-generating fabric, which comprises the composite fabric, conductive coils and clothing described above, wherein the composite fabric and conductive coils are respectively arranged on the clothing, preferably at relative positions of the clothing, and generate electricity by utilizing the interaction during human body movement.
[0137] The conductive coil is selected from one or more organic conductive fibers directly spun from polymer conductive materials such as carbon fiber, carbon nanotube, Mxene, copper (bare copper, also known as red copper or brass, tin-plated copper, silver-plated copper), aluminum, silver, gold, stainless steel wire, nickel and cadmium sulfide, iodide or oxide, polyacetylene, polyaniline, polypyrrole, polythiophene, etc. The specific preparation method is to coat one or more polymer conductive materials such as carbon fiber, carbon nanotube, Mxene, copper (bare copper, also known as red copper or brass, tin-plated copper, silver-plated copper), aluminum, silver, gold, stainless steel wire, nickel and cadmium sulfide, iodide or oxide, polyacetylene, polyaniline, polypyrrole, polythiophene, etc. with cotton threads of various colors such as white, gray, black, yellow, red, blue, light blue, dark blue, green, cyan, purple, etc.
[0138] In one embodiment, the surface magnetism of the power-generating textile after magnetization is 0.1-35 mT.
[0139] For example, the surface magnetism of the power-generating textile after magnetization can be 0.1mT, 1mT, 5mT, 10mT, 15mT, 20mT, 25mT, 30mT, 35mT, etc.
[0140] The higher the surface magnetism of the power-generating fabric after magnetization, the stronger the magnetic property is, and the stronger the power generation capacity is.
[0141] Among them, Mxene is a type of two-dimensional inorganic compound composed of transition metal carbides, nitrides or carbonitrides with a thickness of several atomic layers. From the perspective of morphology, it looks like a hydrogel flattened in the middle of a metal oxide. It has strong conductivity and can completely replace copper and aluminum in wires. In this way, the resistance to ion movement will be much smaller.
[0142] The composite fabric and the conductive coil are fixed on clothing, for example, fixed on the inside of the arm of the clothing or between the legs. The clothing can generate electricity through the swinging of the arms or the alternating movements of the legs, thereby converting the mechanical energy of the human body into electrical energy for powering the equipment. This can be applied to different fields, thereby powering electronic equipment in different fields.
[0143] Example
[0144] The present invention provides general and / or specific descriptions of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % represents wt%, i.e., weight percentage. The reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be obtained commercially.
[0145] Example 1-1 Preparation of composite fibers
[0146] (1) Take 10 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 90g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB particles are dried in air to obtain NdFeB particles. 2 Fe 14 B) A composite material with a particle doping concentration of 90 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0147] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 90wt.%, and a circular cross-section of the fiber, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0148] Example 1-2 Preparation of composite fibers
[0149] (1) Take 10 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 90g of ferrosoferric oxide (Fe 3 O 4 ), a uniformly mixed solution was obtained by stirring and ultrasonication, and after the solvent was completely evaporated, ferroferric oxide (Fe 3 O 4 ) A composite material with a doping concentration of 90wt.%, wherein the vacuum drying temperature is 80°C and the time is 24h.
[0150] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) A composite fiber with a particle doping concentration of 90wt.% and a circular fiber cross-section, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0151] Example 1-3 Preparation of composite fibers
[0152] (1) Take 10 g of dry thermoplastic polyurethane elastomer (TPU) pellets and dissolve them in N,N-dimethylformamide (C 3 H 7 NO) solvent, add 90g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A magnetic composite material with a particle doping concentration of 90 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0153] (2) The magnetic composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) A magnetic composite fiber with a particle doping concentration of 90 wt.%, wherein the twin-screw extrusion temperature is 180°C, the twin-screw main engine speed is 3000 r / min, the winding speed is 6000 r / min, and the diameter of the prepared power generation composite fiber is 50 μm.
[0154] Examples 1-4
[0155] (1) Take 10 g of dry thermoplastic polyurethane elastomer (TPU) pellets and dissolve them in N,N-dimethylformamide (C 3 H 7 NO) solvent, add 90g of ferroferric oxide (Fe 3 O 4 ), a uniformly mixed solution was obtained by stirring and ultrasonication, and after the solvent was completely evaporated, ferroferric oxide (Fe 3 O 4 )A magnetic composite material with a doping concentration of 90wt.%, wherein the vacuum drying temperature is 80°C and the time is 24h.
[0156] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain Fe 3 O 4 The composite fiber has a doping concentration of 90wt.%, wherein the twin-screw extrusion temperature is 180°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0157] Example 1-5 Preparation of composite fibers
[0158] (1) Take 10 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 90g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 90 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0159] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 90wt.%, and a circular cross-section of the fiber, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 7000r / min, and the diameter of the prepared power generation composite fiber is 20μm.
[0160] Example 1-6 Preparation of composite fibers
[0161] (1) Take 10 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 90g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 90 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0162] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 90wt.%, and a circular cross-section of the fiber, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 5500r / min, and the diameter of the prepared power generation composite fiber is 80μm.
[0163] Example 1-7 Preparation of composite fibers
[0164] (1) Take 10 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 90g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 90 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0165] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 90wt.%, and a circular cross-section, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 5000r / min, and the diameter of the prepared power generation composite fiber is 100μm.
[0166] Example 1-8 Preparation of composite fibers
[0167] (1) Take 10 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 90g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 90 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0168] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fibers with a particle doping concentration of 90 wt.%, and a circular cross-section, wherein the twin-screw extrusion temperature is 210° C., the twin-screw main engine speed is 3000 r / min, the winding speed is 4500 r / min, and the diameter of the prepared power generation composite fiber is 200 μm.
[0169] Example 1-9 Preparation of composite fibers
[0170] (1) Take 10 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 90g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 90 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0171] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fibers with a particle doping concentration of 90 wt.%, and a circular cross-section, wherein the twin-screw extrusion temperature is 210° C., the twin-screw main engine speed is 3000 r / min, the winding speed is 4000 r / min, and the diameter of the prepared power generation composite fiber is 500 μm.
[0172] Example 1-10 Preparation of composite fibers
[0173] (1) Take 15 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 85g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 85 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0174] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 85wt.%, and a circular cross-section, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0175] Example 1-11 Preparation of composite fibers
[0176] (1) Take 20 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 80g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 80 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0177] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 80wt.%, and a circular cross-section of the fiber, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0178] Example 1-12 Preparation of composite fibers
[0179] (1) Take 25 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 75g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 75 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0180] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 75wt.%, and a circular cross-section of the fiber, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0181] Example 1-13 Preparation of composite fibers
[0182] (1) Take 50 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 50g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 50 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0183] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 50wt.%, and a circular cross-section of the fiber, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0184] Example 1-14 Preparation of composite fibers
[0185] (1) Take 75 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 25g of neodymium iron boron (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 25 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0186] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 25wt.%, and a circular cross-section. The twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0187] Example 1-15 Preparation of composite fibers
[0188] (1) Take 90 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 10g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 10 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0189] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 10 wt.%, and a circular cross-section. The twin-screw extrusion temperature is 210° C., the twin-screw main engine speed is 3000 r / min, the winding speed is 6000 r / min, and the diameter of the prepared power generation composite fiber is 50 μm.
[0190] Example 1-16 Preparation of composite fibers
[0191] (1) Take 99.9 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 0.1g NdFeB (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 0.1 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0192] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 0.1wt.%, and a circular cross-section. The twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0193] Example 1-17 Preparation of composite fibers
[0194] (1) Take 10g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles, dissolve them in cycloolefin copolymer (COC) solvent, add 90g of neodymium iron boron (Nd 2 Fe 14 B) particles, and a uniformly mixed solution is obtained by stirring and ultrasonication. After the solvent is completely evaporated, the NdFeB (Nd 2 Fe 14 B) A composite material with a particle doping concentration of 90 wt.%, wherein the vacuum drying temperature is 80° C. and the time is 24 h.
[0195] (2) The composite material obtained in (1) is processed into small pieces, and then subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) Composite fiber with a particle doping concentration of 90wt.%, and a circular cross-section of the fiber, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000r / min, the winding speed is 6000r / min, and the diameter of the prepared power generation composite fiber is 50μm.
[0196] Example 1-18 Preparation of composite fibers
[0197] (1) Take 25g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and add 75g of neodymium iron boron (Nd 2 Fe 14 B) Granules were granulated and mixed 10 times using a twin-screw extruder.
[0198] (2) The mixed particles obtained in (1) are subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) A composite fiber with a doping concentration of 75 wt.%, wherein the twin-screw extrusion temperature is 210°C, the twin-screw main engine speed is 3000 r / min, the winding speed is 6000 r / min, and the diameter of the prepared power generation composite fiber is 50 μm.
[0199] Example 1-19 Preparation of composite fibers
[0200] (1) Take 25g of dry thermoplastic polyurethane elastomer (TPU) particles and add 75g of neodymium iron boron (Nd 2 Fe 14 B) Granules were granulated and mixed 10 times using a twin-screw extruder.
[0201] (2) The mixed particles obtained in (1) are subjected to twin-screw extrusion, water bath cooling, and winding to obtain NdFeB (Nd 2 Fe 14 B) A composite fiber with a doping concentration of 75 wt.%, wherein the twin-screw extrusion temperature is 180°C, the twin-screw main engine speed is 3000 r / min, the winding speed is 6000 r / min, and the diameter of the prepared power generation composite fiber is 50 μm.
[0202] Example 1-20 Preparation of composite fibers
[0203] (1) Take 20 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 80g NdFeB (Nd 2 Fe 14 B) particles, and a uniform mixture of NdFeB (Nd 2 Fe 14 B) Solution with particle doping concentration of 80 wt.%.
[0204] (2) The mixed solution is used as the spinning solution, and is squeezed out from the injection pump into the coagulation bath by a stepper motor. In the coagulation bath, the solvent and the coagulant are exchanged, so that the extruded polymer mixed solution is rapidly coagulated. A stretching and traction device is set on the other side. With the extrusion of the injection pump and the traction and winding of the stretching device, the neodymium iron boron (NdFeB) is obtained. 2 Fe 14 B) The particle doping concentration of the composite fiber is 80 wt.%, and the diameter of the prepared power generation composite fiber is 40 μm.
[0205] Example 1-21 Preparation of composite fibers
[0206] (1) Take 25 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 75g NdFeB (Nd 2 Fe 14 B) particles, and a uniform mixture of NdFeB (Nd 2 Fe 14 B) Solution with particle doping concentration of 75 wt.%.
[0207] (2) The mixed solution is used as the spinning solution, and is squeezed out from the injection pump into the coagulation bath by a stepper motor. In the coagulation bath, the solvent and the coagulant are exchanged, so that the extruded polymer mixed solution is rapidly coagulated. A stretching and traction device is set on the other side. With the extrusion of the injection pump and the traction and winding of the stretching device, the neodymium iron boron (NdFeB) is obtained. 2 Fe 14 B) The particle doping concentration of the composite fiber is 75 wt.%, and the diameter of the prepared power generation composite fiber is 40 μm.
[0208] Example 1-22 Preparation of composite fibers
[0209] (1) Take 75 g of dry styrene-ethylene-butylene-styrene block copolymer (SEBS) particles and dissolve them in cyclohexane (C 6 H 12 ) solvent, add 25g of neodymium iron boron (Nd 2 Fe 14 B) particles, and a uniform mixture of NdFeB (Nd 2 Fe 14 B) Solution with particle doping concentration of 25 wt.%.
[0210] (2) The mixed solution is used as the spinning solution, and is squeezed out from the injection pump into the coagulation bath by a stepper motor. In the coagulation bath, the solvent and the coagulant are exchanged, so that the extruded polymer mixed solution is rapidly coagulated. A stretching and traction device is set on the other side. With the extrusion of the injection pump and the traction and winding of the stretching device, the neodymium iron boron (NdFeB) is obtained. 2 Fe 14 B) The particle doping concentration of the composite fiber is 25 wt.%, and the diameter of the prepared power generation composite fiber is 30 μm.
[0211] Comparative Example 1 Preparation of composite fibers
[0212] The difference between Comparative Example 1 and Examples 1-12 is that Comparative Example 1 uses a hot melt method, that is, it is prepared using the method of Example 1 in Application No. 202010567156.3.
[0213] Table 1 Process conditions of Examples 1-1 to 1-19
[0214]
[0215] Example 2-1 Preparation of power generating fabric
[0216] The composite fiber obtained in Example 1-1 is coated with yellow cotton thread, and then the coated composite fiber is woven by warp and weft weaving using a rapier loom to obtain a magnetic composite fabric;
[0217] A copper wire (Cu) with a diameter of 50 μm was coated with yellow cotton thread, and the coated copper wire was sewn to the inner arm of the jacket using a computer embroidery machine as a conductive coil in a spiral shape;
[0218] The magnetic composite fabric is fixed on the opposite side of the conductive coil on the clothing to obtain a power-generating top.
[0219] Preparation of power generation fabrics in Examples 2-2 to 2-22
[0220] The composite fibers obtained in Examples 1-2 to 1-22 were respectively prepared according to the method described in Example 2-1 to obtain power-generating tops 2-2 to 2-22.
[0221] Comparative Example 2 Preparation of Power Generation Fabric
[0222] The composite fiber described in Comparative Example 1 was prepared according to the method described in Example 2-1 to obtain a power-generating top.
[0223] Experimental Example 1 Performance Measurement of Composite Fiber
[0224] A. Determination of single-point remanence on the composite fiber surface
[0225] The single-point remanence of the composite fibers described in Examples 1-1 to 1-22 and Comparative Example 1 was measured, and the measurement results are shown in Table 2, wherein the single-point remanence was measured by using a Gaussmeter to measure the remanence at multiple points on the surface of the composite fiber, and taking their average value as the single-point remanence of the composite fiber.
[0226] Table 2 Measurement results of single-point remanence on the surface of composite fibers
[0227]
[0228]
[0229] It can be seen from Table 2 that the remanence of the composite fiber of the present invention is relatively high, indicating that the stronger the magnetic properties of the composite fiber obtained by the present invention, the better the effect.
[0230] B. The composite fibers described in Examples 1-1 to 1-22 and Comparative Example 1 were subjected to the measurement of the breaking stress and the breaking strain, and the results are shown in Table 3, wherein the method for measuring the breaking stress is: using a universal mechanical testing machine to measure the final stress magnitude when the sample is completely broken;
[0231] The method for measuring the breaking strain is: using a universal mechanical testing machine to measure the maximum elongation of the sample before it is completely broken.
[0232] Table 3 Measurement results of breaking stress and breaking strain of composite fibers
[0233]
[0234]
[0235] It can be seen from Table 3 that the composite fiber of the present invention has good breaking stress and breaking strain, indicating that the composite fiber obtained by the present invention has good strain performance.
[0236] Experimental Example 2 Performance Measurement of Power Generation Fabric
[0237] The surface magnetism and peak voltage of the power-generating fabrics obtained in Examples 2-1 to 2-22 and the power-generating fabrics obtained in Comparative Example 2 were measured, and the measurement results are shown in Table 4, wherein the surface magnetism was measured as follows: a Gaussmeter was used to measure the surface magnetism of multiple points on the surface of the magnetic fabric, and their average value was taken as the surface magnetism of the magnetic fabric.
[0238] The peak voltage is measured as follows: fix the generating fabric on the X-axis slider of the ball screw three-axis slide, fix the copper wire coil (1000 turns) at 1 mm away from the opposite side of the fabric, connect both ends of the coil to the oscilloscope, and connect the oscilloscope to the computer, make the ball screw X-axis slider reciprocate 20 times along the X-axis at a speed of 300 m / s, with a one-way distance of 20 cm, and take the maximum voltage displayed on the computer as the peak voltage.
[0239] Table 4 Measurement results of surface magnetism and peak voltage of magnetic fabric
[0240]
[0241]
[0242] It can be seen from Table 4 that the surface magnetism of the fabric obtained by the present invention is higher, the magnetism is stronger, and it can continuously output voltage and current, thereby realizing the power generation capacity of clothing and supplying power to electronic equipment in various fields.
[0243] In summary, the composite fiber described in the present invention has a high concentration of magnetic particles, the resulting composite fiber has a high remanence, good magnetic properties, and good strain performance. In addition, the resulting fabric has a high surface magnetism. By fixing the composite fabric and the conductive coil on the clothing and through movement, the clothing can generate electricity, thereby converting the mechanical energy of the human body into electrical energy for powering the equipment, thereby realizing power supply for electronic equipment in different fields.
[0244] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite fiber, comprising the following steps: Compounding metal micro-nano particles and polymer base materials to obtain composite materials; Extruding the composite material through a twin-screw extruder to obtain composite fibers; The metal micro-nano particles are metal alloy magnetic micro-nano particles; The metal alloy magnetic micro-nano particles are Nd2Fe 14 B magnetic particles, the particle size of the metal micro-nano particles is 5 μm; The polymer base material is a thermoplastic polymer, which is a thermoplastic polyurethane elastomer (TPU) and / or a styrene-ethylene / butylene-styrene block copolymer (SEBS); The metal micro-nano particles account for 80-90% by mass in the composite material; In the step of obtaining the composite material, the metal micro-nano particles and the polymer base material are chemically dissolved to obtain the composite material, wherein the chemical dissolution is to put the metal micro-nano particles and the polymer base material into a solvent for dissolution, and then remove the solvent to obtain the composite material; The solvent is selected from one or more of dimethylacetamide, chloroform, ether, acetone, N,N-dimethylformamide, ethylene glycol, propylene glycol, ethanol, isopropanol, ethyl acetate, cyclohexane and xylene.
2. The method according to claim 1, wherein: The twin-screw main engine has a rotation speed of 100-6000 r / min.
3. The method according to any one of claims 1 to 2, wherein: In the step of preparing the composite fiber, after extrusion using a twin-screw extruder, a winding step is also included before obtaining the composite fiber.
4. The method according to claim 3, wherein: The winding speed is 100-6000 r / min.
5. A composite fiber prepared by the method according to any one of claims 1 to 4, wherein the diameter of the composite fiber is 20 to 500 μm.
6. The composite fiber according to claim 5, wherein The diameter of the composite fiber is 20-100 μm.
7. The composite fiber according to claim 5, wherein The breaking stress of the composite fiber is 0.1-100.0 MPa.
8. The composite fiber according to claim 5, wherein The breaking strain of the composite fiber is 101-800%.
9. The composite fiber according to claim 5, wherein The single-point remanence of a single fiber in the composite fiber after magnetization is 0.1-16 mT.
10. The composite fiber according to claim 5, wherein The cross section of a single fiber in the composite fiber is selected from the following: circular, circular ring, triangle, triangular ring, rectangle, rectangular ring and irregular shape.
11. A composite fabric, wherein: The composite fabric is obtained by weaving the composite fiber according to any one of claims 5 to 10.
12. The composite fabric according to claim 11, wherein: The composite fiber is covered with cotton thread.
13. The composite fabric according to claim 11 or 12, wherein: The composite fabric is a plain fabric, a twill fabric or a satin fabric.
14. A power generating fabric, wherein: The power generating fabric comprises the composite fabric, conductive coil and clothing according to any one of claims 11 to 13, wherein the composite fabric and conductive coil are respectively arranged on the clothing.
15. The power generating textile according to claim 14, wherein: The composite fabric and the conductive coil are arranged at relative positions on the garment.
16. The power generating textile according to claim 14, wherein: The conductive coil is selected from one or more of carbon fiber, carbon nanotube, MXene, copper, silver, gold, stainless steel wire, polyacetylene, polyaniline, polypyrrole and polythiophene.
17. The power generating textile according to any one of claims 14 to 16, wherein: The surface magnetism of the power-generating fabric after magnetization is 12-35 mT.
